To solve the equation (x + 12)² = 9 using square roots, we can first take the square root of both sides of the equation. This will give us:
√((x + 12)²) = √9
Simplifying this equation, we have:
x + 12 = ±3
Now, we can solve for x by subtracting 12 from both sides of the equation:
x = -12 ± 3
This gives us two possible solutions:
x = -12 + 3 = -9
x = -12 - 3 = -15
So, the correct answer is:
{-9,-15}
Solve the following quadratic equation using square roots: (x + 12)² = 9
• {-9,-15}
• {15,9}
• {-3,-21}
• {-7.5, -16.5}
1 answer